Analysis of performance company : Based on Value Added and Financial Statement - Pernamasari, Rieke (Universitas Pendidikan Indonesia, 2020)
This research is the concept of proving the function and / or important factors analytically and experimentally. This study aims to analyze investment decisions as measured by stock prices with performance measures as the independent variable. Company performance measures measured through economic value added (EVA), market value added (MVA), Return on Equity (ROE), and Earning Per Share (EPS). The research method used is quantitative research and the sample of this study is an investor index company listed on the Indonesia Stock Exchange (BEI) in 2015 - 2018. The method of analysis used is multiple regression test. The results of this study indicate that EVA and MVA have no effect on stock prices, while ROE and EPS have an effect on stock prices. So it can be denied that investors in Indonesia, company investors 33, look at the figures shown in historical financial reports more than they look at the residual income.